2020
DOI: 10.1108/jadee-11-2018-0160
|View full text |Cite
|
Sign up to set email alerts
|

Contract farming and rice production efficiency in Ghana

Abstract: PurposeEven though many studies identify positive effects of contract farming (CF) on the livelihood of farmers, the use of CF as a tool to increase farm performance is unsettled debate. Information on CF is relatively not available in staple food chains. Theoretical considerations have shown that there are challenges in employing CF in staple food chains such as rice. With the increasing trend of rice CF in Ghana, it is very critical to establish its performance in rice production in Ghana. It is therefore im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In recent years, many studies addressed the topic of vertical coordination of other agricultural products in China (Mwambi et al, 2016;Yan et al, 2017;Orr 2018;Bidzakin et al, 2020), but they did not focus on the topics of grape or wine production and dragon head enterprises in the context of vertical coordination. Huang et al (2009) show that changes in the mid-to downstream segments of the Chinese economy took place.…”
Section: Literature Review On Vertical Coordination In Fresh Fruits and Vegetables In Chinamentioning
confidence: 99%
“…In recent years, many studies addressed the topic of vertical coordination of other agricultural products in China (Mwambi et al, 2016;Yan et al, 2017;Orr 2018;Bidzakin et al, 2020), but they did not focus on the topics of grape or wine production and dragon head enterprises in the context of vertical coordination. Huang et al (2009) show that changes in the mid-to downstream segments of the Chinese economy took place.…”
Section: Literature Review On Vertical Coordination In Fresh Fruits and Vegetables In Chinamentioning
confidence: 99%
“…In Ghana and Africa at large, most of the work that have been done on inter-organizational relationships pertain to contract farming (e.g., Grosh, 1994; Porter and Phillips-Howard, 1997; Bijman, 2008; Oya, 2012; Poku et al ., 2018; Ragasa et al , 2018; Adabe et al , 2019; Dubbert, 2019; Bidzakin et al , 2020). Specific studies in Ghana include those that assess the formal (written) and informal (verbal) contracts (Poku et al , 2018; Abdul-Rahaman and Abdulai, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies reported that contract farming is an institutional arrangement used to improve smallholder farmers' market access by providing agricultural raw materials to improve TE [5][6][7][8]. Research studies note that smallholder farmers participate in contract farming to reduce the risk associated with production to processors and put the subject cost burden-i.e., seed, pesticides, and fertilizer-on the processor and/or exporters [9,10]. According to recent studies [5][6][7][8], contract farming offers farmers higher productivity and increases their market access.…”
Section: Introductionmentioning
confidence: 99%